Placemaking : people, properties, planning - Higgins, David; Larkham, Peter J. (Emerald Publishing Limited, 2024)
Placemaking: People, Properties, Planning, delivers a cross-disciplinary critique of "placemaking", an approach to the design and creation of new urban places, and the reshaping of old ones, that has become so pervasive that it forms the 'strapline' for the UK's Royal Town Planning Institute. Developing principally from planning and urban design, placemaking has swiftly become a new orthodoxy, a dominant paradigm. It seems to be all-encompassing, particularly at a time when towns and cities face new and large-scale challenges relating to climate change, sustainability, population movement and intensive capital regeneration. Higgins and Larkham alongside an expert team of contributors examine the experiences of placemaking, the underlying principles and motivations of placemaking, the importance of context, the quality of the places produced, and the experiences of those living and working in them. Placemaking: People, Properties, Planning contains a series of short, sharp chapters exploring a broad range of placemaking concepts and experiences. It is designed to be critical, but easily comprehensible to both university-level students in built environment academic disciplines and to practitioners in related professions.